2010
DOI: 10.4067/s0718-07642010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Utilización de Residuos Forestales Lignocelulósicos para Producción del Hongo Ostra (Pleurotus ostreatus)

Abstract: ResumenSe estudió el potencial de distintos residuos forestales como sustrato para el cultivo del hongo Pleurotus ostreatus. Para ello, se analizó la composición química de estos residuos, antes y después de la etapa de cosecha, y se midieron distintas variables fenológicas y morfológicas así como el rendimiento y la calidad de los cuerpos fructíferos de Pleurotus ostreatus tras la cosecha. Se fijaron cuatro tratamientos: astillas de álamo, astillas de eucalipto, mezcla de paja de trigo y eucalipto, y paja de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
0
7
0
11
Order By: Relevance
“…Crop of mushrooms (Pleurotus ostreatus) it is a source of products agricultural, their organic waste generated can be used as a source of food with high protein content and as an alternative pharmaceutical treatment; Pleurotus ostreatus is a fungus that has the ability to grow on agricultural wastes, accelerates the biodegradation and recycling them, avoiding its burning and the subsequent environmental pollution (Varnero, Quiroz, & Álvarez, 2010). Lentinula edodes, fungi edible, is the most studied, has been shown that fruiting body and mycelium have antimicrobial properties; likewise, the lentine inhibits mycelium growth of other fungi as Physalospora piricola, Mycosphaerella arachidicola and Botrytis cinerea (Rojas, 2013;Romero-Arenas, Martínez, Damian, Ramírez, & López-Olguín, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Crop of mushrooms (Pleurotus ostreatus) it is a source of products agricultural, their organic waste generated can be used as a source of food with high protein content and as an alternative pharmaceutical treatment; Pleurotus ostreatus is a fungus that has the ability to grow on agricultural wastes, accelerates the biodegradation and recycling them, avoiding its burning and the subsequent environmental pollution (Varnero, Quiroz, & Álvarez, 2010). Lentinula edodes, fungi edible, is the most studied, has been shown that fruiting body and mycelium have antimicrobial properties; likewise, the lentine inhibits mycelium growth of other fungi as Physalospora piricola, Mycosphaerella arachidicola and Botrytis cinerea (Rojas, 2013;Romero-Arenas, Martínez, Damian, Ramírez, & López-Olguín, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These same researchers (Pardo et al 2007), grew P. ostreatus on substrates of a varied lignocellulosic nature (cereal straw, kenaf, vine shoot, and “alperujo”) that were subjected to various treatments (pasteurization and thermophilic conditions, moisturizing with benomyl and pasteurization and fermentation semi-anaerobic); they reached values between 0.87 cones/hole, for the combination of straw and “alperujo” 1:1 (v/v) and 1.35 cones/hole for mixing straw and kenaf, and between 0.70 cones/hole, with pasteurization and thermophilic conditions and 1.52 cones/hole in semi-anaerobically fermented substrates. Varnero et al (2010), with P. ostreatus cultivated on WS substrates, eucalyptus chips, slivers of poplar, and mixture of WS and eucalyptus chips; they came to achieve in 1 kg of substrate, a cluster number that ranged from 2.8 (poplar chips) to 5.2 (WS).…”
Section: Resultsmentioning
confidence: 99%
“…No supplementation is enhanced by supplementation of 600 g in WS + SPS and SPS. Varnero et al (2010) in 1 kg of substrate achieved from 3.4 carpophores only (poplar chips) to 18.2 fruiting bodies of the oyster mushroom. Pardo et al (2005a) show values ranging from 42 mushrooms/package of 15 kg to 80 mushrooms/package of 15 kg, depending on type of mycelium, substrates nature, and treatment of substrates to which they are subjected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalmente, los residuos de la industria maderera son incinerados para generación de energía y calefacción, o son dispuestos finalmente como basura, siendo una fuente potencial de biomasa renovable para producir etanol. Las alternativas de aprovechamiento implementadas hasta el momento se han enfocado fundamentalmente hacia su recuperación energética (Varnero et al, 2010).…”
Section: Metodologíaunclassified